2022
DOI: 10.3389/fnhum.2022.902731
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis and research progress in leukoaraiosis

Abstract: Leukoaraiosis is a common imaging marker of cerebral small vessel disease. In recent years, with the continuous advances in brain imaging technology, the detection rate of leukoaraiosis is higher and its clinical subtypes are gradually gaining attention. Although leukoaraiosis has long been considered an incidental finding with no therapeutic necessity, there is now growing evidence linking it to, among other things, cognitive impairment and a high risk of death after stroke. Due to different research methods,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 158 publications
0
8
0
Order By: Relevance
“…Cumulative evidence demonstrated that WMLs was associated with an increased risk of symptomatic stroke, cognitive impairment, and death. 25,26 In our study, we found that 44.9% of patients who suffered an ischemic stroke present with moderate-severe WMLs. These results broadly agree with the findings of previous studies.…”
Section: Discussionmentioning
confidence: 52%
“…Cumulative evidence demonstrated that WMLs was associated with an increased risk of symptomatic stroke, cognitive impairment, and death. 25,26 In our study, we found that 44.9% of patients who suffered an ischemic stroke present with moderate-severe WMLs. These results broadly agree with the findings of previous studies.…”
Section: Discussionmentioning
confidence: 52%
“…Unfortunately, neuroimaging findings regarding the presence of microbleeds or white matter hyperintensities were not available for analysis in our study. Yet, the correlation of b‐SICH and r‐SICH with age may be partly interpreted through the prism that the prevalence of both microbleeds and leukoaraiosis consistently increase with age [34–36]. Furthermore, with regard to previous ischaemic lesions, a history of previous stroke or TIA was indeed more frequent in patients with r‐SICH compared to l‐SICH.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a previous study found patients with transient ischemic attack within 3 days of onset show an increase in choline ( Bisschops et al, 2002 ). Ischemia or hypometabolism are also potential pathogenic mechanisms for LA ( Sun et al, 2022 ). In the subgroup analysis, the level of tCho showed no significant increase in mild WMHs subgroup patients compared to healthy controls, which suggests that mild cerebral white matter hyperintensities do not cause changes in the level of tCho until the disease has progressed to a certain level.…”
Section: Discussionmentioning
confidence: 99%